New records of shy-type albatrosses Thalassarche cauta/T. steadi off the Argentine Continental Shelf - Seco Pon, Juan Pablo (2013)
Shy Thalassarche cauta and White-capped albatrosses T. steadi are two taxa for which specific status has recently been posited, however, owing to their morphological resemblance they are frequently referred to as “shy-type” albatrosses. Information on the distribution of this albatross complex in the Argentine Continental Shelf is particularly scarce and limited to only a few observations, chiefly obtained in the Argentine-Uruguayan Common Fishing Zone and in the vicinity of the Malvinas (Falkland) Islands; there is virtually no information for other oceanic areas (continental shelf, shelf-break area and slope). New records of shytype albatrosses were obtained during the development of project assessments of the interaction between commercial trawl fisheries and seabirds attending waters of the Argentine Continental Shelf. The observation effort (counts during trawling operations) covered all seasons in a four-year span. These records provide new information on the presence and abundance of this albatross complex for a wide latitudinal range off Argentina that is also an area of operation of trawling fishing fleets (e.g. Argentine hake fishery). The records presented here add to the recent body of evidence demonstrating that individuals of T. cauta/steadi, especially immatures, and to some extent non-breeding adults, attend waters of the southern South Atlantic, where they associate with commercial trawlers in Argentina.